SOCIO-CULTURAL FOUNDATIONS OF GENESIS PHILOSOPHICAL THOUGHT OF THE KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article discusses the sociocultural foundations of the genesis of the worldview,the paradigm of mythological consciousness, the positive elements of pre-Muslim beliefs andempirical knowledge of the ancient Kyrgyz. It is noted that positive trends in the worldview ofthe ancient Kyrgyz were manifested in myths, early forms of religion and empirical knowledge.Everyday practice and observations determined the formation of initial rational tendencies in thethinking of people, their main feature was a contemplative attitude towards the outside world, theunity of which was spontaneously recognized by our ancestors.
Keywords: philosophy, society, nature, thought, man, myth, religion, knowledge, faith, people, consciousness.